PMSM drive using silicon carbide inverter: Design, development and testing at elevated temperature - Singh S.K.; Pilli N.K.; Guedon F.; McMahon R. (My University, 2025)
With the development in silicon carbide (SiC) power device technology, the prospects of SiC to replace silicon (Si) in HEVs are increasing. Through this paper the authors have tried to highlight the practical challenges associated with the thermal aspect and switching EMI of SiC inverter. To assess the quality of upcoming devices, a statistical analysis of the normally-on SiC JFETs is performed. Experimentally the SiC devices in a voltage source inverter (VSI) topology are exploited to operate at higher case temperature of 105°C. Instead using additional Schottky diodes across the SiC devices, the intrinsic PiN body diodes are utilised, reducing the number of components. The size and cost of the SiC inverter is reduced by removing the LC filter at the output stage of the VSI driving a permanent magnet synchronous machine (PMSM). © 2015 IEEE.